2001
DOI: 10.1002/jnr.1122
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution, calmodulin interaction, and mitochondrial association of the hyaluronan‐binding protein RHAMM in rat brain

Abstract: The CNS contains high levels of the glycosaminoglycan hyaluronan, and neural cells express a variety of proteins that are members of the hyaladherin family of hyaluronan-binding proteins. We have previously shown that the hyaladherin RHAMM (receptor for hyaluronan-mediated motility; CD168) is expressed by neural cells in culture; plays a role in astrocyte motility, neurite migration, and axonal growth; and is widely distributed in neurons and oligodendrocytes of developing and adult rat CNS. Here we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 69 publications
1
36
0
Order By: Relevance
“…For example, RHAMM is required for activation of signaling pathways through IL-1␤ and TNF-␣, such as erk, and AP-1 (14,19). RHAMM also binds to calmodulin (16), regulates connexin expression (43), and promotes formation of diacylgycerol in response to hyaluronan, linking this hyaladherin to phospholipase C␥ (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, RHAMM is required for activation of signaling pathways through IL-1␤ and TNF-␣, such as erk, and AP-1 (14,19). RHAMM also binds to calmodulin (16), regulates connexin expression (43), and promotes formation of diacylgycerol in response to hyaluronan, linking this hyaladherin to phospholipase C␥ (44).…”
Section: Discussionmentioning
confidence: 99%
“…RHAMM is expressed on the cell surface (where it is designated CD168) and in the cytoplasm, as well as in the cytoskeleton and nucleus. Like CD44, RHAMM is subject to alternative splicing (14)(15)(16)(17), particularly during tissue repair or after neoplastic conversion (17). After its interaction with HA, this receptor delivers signals for cell migration and proliferation in normal and malignant cells (15,(17)(18)(19).…”
mentioning
confidence: 99%
“…It has been demonstrated that RHAMM is associated with tubulin and actin cytoskeletal elements (10,23), indicating that RHAMM may be important to the movement and reorganization of blastomeres during early embryonic development. RHAMM has also been reported to be associated with cytoskeletal interaction of mitochondria, thus, it may regulate mitochondrial motility and positioning (24), which is important for the physiological process of cytoplasmic maturation and the further development of mammalian oocytes (25). In addition, RHAMM regulates Ras signaling and is involved in breast cancer progression (26).The upregulation of RHAMM is therefore closely involved in regulating tumorigenesis, proliferation, tumor vascular invasion and node metastasis of HCC cells.…”
Section: Disease-free Survival (Months)mentioning
confidence: 99%
“…The mitoplasts were recovered by centrifugation at 4000 g and then resuspended in 10 mM HEPES-KOH, pH 7.4, containing 220 mM mannnitol and 70 mM sucrose. Alkaline extraction with carbonate buffer was performed as described previously (Lynn et al, 2001). Briefly, mitochondria and mitoplasts were resuspended in 100 mM sodium carbonate pH 11 for 30 minutes at 4°C, then centrifuged at 100,000 OGT localizes to mitochondria g for 30 minutes.…”
Section: Biochemical Isolation and Separation Of Hela Cellsmentioning
confidence: 99%